Perlindungan Hukum Terhadap Anak Korban Pelecehan Seksual dalam Perspektif Keadilan Restoratif - Chepi Ali Firman Zakaria; Ade Mahmud; Aji Mulyana (Jurnal Penelitian Hukum De Jure, 2023)
Sexual violence against child is a global problem today. Although international instruments have been ratified, they do not guarantee the realization of the rights of child victims. One reason is that not all countries’ legal systems support victims. The principles of redress for victims of child sexual violence are set out in the United Nations Convention on the Rights of the Child. The Convention recognizes the principle of non-discrimination, the best interests of the child, child survival and development, and values Child opinions. The problem you encountered is related to 1) your security system. 2). Reintegration, psychosocial support, treatment and recovery, protection and support in court proceedings. A model of restorative justice that protects the rights of victims of child sexual violence can use the victim-offender mediation model. This model provides an opportunity for communities to come together and find solutions together when offenders are willing to admit their mistakes and take responsibility according to the needs of the victim’s child. The implications of this research are hoped to make a real contribution to the nation by providing better protection for children who are victims of sexual violence and reducing the trauma they experience.